1997
DOI: 10.1063/1.119975
|View full text |Cite
|
Sign up to set email alerts
|

Self-texturing of nitrogenated amorphous carbon thin films for electron field emission

Abstract: The electron field-emission process for nitrogenated amorphous carbon ͑a-C:H:N͒ thin films deposited using a magnetically confined hydrocarbon plasma is examined. The morphology of the films obtained using an atomic force microscope is compared to the field-emission properties. Beyond a chemical composition of 14 at. % nitrogen, the mirror smooth a-C:H:N films become self-texturing, and multiple ''domelike'' cathodes of nanometer scale are observed. The dimensions of these ''domelike'' cathodes varies with tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 18 publications
2
38
0
Order By: Relevance
“…Previous studies of DLC based field emission devices have shown E T can be as high as 10 -20 V/μm. For example, llie et al 15 have found E T in the range 21 V/μm to 10 V/μm in amorphous carbon films, whereas Silva et al 16 have found E T close to 5 V/μm in nanostructured DLC films having N contents as high as 11 at.% and 15 at.%. Forrest et al 17 examined the effect of the thickness of hydrogenated DLC (a-C:H) and nitrogenated tetrahedral amorphous carbon (ta-C:N) films on the field emission characteristics of their films and found high values of E T in a-C:H films which varied between 60 V/μm and 10 V/μm, though lower values were found in ta-C:N films.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of DLC based field emission devices have shown E T can be as high as 10 -20 V/μm. For example, llie et al 15 have found E T in the range 21 V/μm to 10 V/μm in amorphous carbon films, whereas Silva et al 16 have found E T close to 5 V/μm in nanostructured DLC films having N contents as high as 11 at.% and 15 at.%. Forrest et al 17 examined the effect of the thickness of hydrogenated DLC (a-C:H) and nitrogenated tetrahedral amorphous carbon (ta-C:N) films on the field emission characteristics of their films and found high values of E T in a-C:H films which varied between 60 V/μm and 10 V/μm, though lower values were found in ta-C:N films.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Thin amorphous carbon films are a possible cold cathode material [4][5][6] for use in FPDs. For this to come to fruition the lifetime and emission site density of these materials needs to be maximized for low operating electric fields to levels at which a display device may be technically and commercially viable.…”
Section: ͓S0003-6951͑98͒03351-8͔mentioning
confidence: 99%
“…The amorphous carbon nitride films obtained are, themselves, useful because they have properties such as high hardness and wear resistivity, chemical inertness, lack of magnetic response and optical gap ranging from zero to a few electron-volts, depending upon the nitrogen concentration and deposition conditions. 14,15 A few of the experimental studies resulted in polycrystalline material, 5 -7,9,16 whereas some authors claimed to have produced nanocrystallites embedded in an amorphous matrix 11,13 showing the expected crystal structure ofˇ-C 3 N 4 .…”
mentioning
confidence: 97%